2008
DOI: 10.1300/j512v13n03_02
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Corn Gluten Meal on Direct-Seeded Vegetable Seedling Establishment

Abstract: Corn gluten meal (CGM) may be used as a preemergent or preplant-incorporated herbicide for organic weed control of young C. L. Webber III developing or emerging weed seedlings. Unfortunately, CGM can also adversely impact seedling survival of certain direct-seeded vegetable crops. Various vegetable crop seedlings respond differently to CGM applications, and the impact of CGM applications on direct-seeded cucurbit crops or dry beans has not yet been determined. Field research was conducted in southeast Oklahoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…Boydston et al (2011) also reported that MSM, 'IdaGold', application rates of 110, 220, and 440 g/m 2 severely reduced onion establishment in a greenhouse study when applied PPI, PRE or at the cotyledon stage. The current research is consistent with the application of corn gluten meal to direct-seed vegetables (black bean (Phaseolus vulgaris L.), pinto bean, cantaloupe, and watermelon by Webber et al (2008). Further research should address banded applications of MSM with either established direct-seeded or transplanted cucurbits, or other vegetable crops in the same manner as others have done with corn gluten meal (Boydston et al, 2011;Webber & Shrefler, 2006;Webber et al, 2007).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Boydston et al (2011) also reported that MSM, 'IdaGold', application rates of 110, 220, and 440 g/m 2 severely reduced onion establishment in a greenhouse study when applied PPI, PRE or at the cotyledon stage. The current research is consistent with the application of corn gluten meal to direct-seed vegetables (black bean (Phaseolus vulgaris L.), pinto bean, cantaloupe, and watermelon by Webber et al (2008). Further research should address banded applications of MSM with either established direct-seeded or transplanted cucurbits, or other vegetable crops in the same manner as others have done with corn gluten meal (Boydston et al, 2011;Webber & Shrefler, 2006;Webber et al, 2007).…”
Section: Discussionsupporting
confidence: 76%
“…Weed research was rated as the number one priority by organic producers (Walz, 2011). Research has been conducted to develop weed control strategies that would qualify as natural, organic, and/or sustainable (Webber & Shrefler, 2008). Naturally occurring chemicals found within plants offer an excellent potential source for natural herbicides for weed control in crops (Rice, 1984).…”
Section: Organic Weed Controlmentioning
confidence: 99%